2015
DOI: 10.1038/ejcn.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the omega-3 fatty acid intake measured by a web-based food frequency questionnaire against omega-3 fatty acids in red blood cells in men with prostate cancer

Abstract: This study has shown that the web-FFQ is an accurate tool to assess total long-chain ω-3 FAs, EPA and DHA but not ALA intake in clinical trials and epidemiological studies carried out in men with PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(51 reference statements)
1
6
0
Order By: Relevance
“…Subsequently, Turcot et al 28 modified an existing 14-item FFQ for use in 137 participants (62% with hyperlipidaemia). They reported adjusted Spearman's correlations for ALA of 0.23 and 0.18 for total n3, with values for EPA and DHA of 0.29 and 0.41 respectively, which were consistent with the range of correlations found by Serra-Majem et al More recently Allaire et al 29 reported higher adjusted Spearman correlations of 0.59, 0.59 and 0.55 for EPA, DHA and LCn3, respectively (P o0.01) using a larger range of questions (136 questions with 40 sub-questions) in a sample of 60 men with prostate cancer. The results from the current study are similar to those of Allaire et al, as would be expected based on the greater number of questions used to identify food intakes related to CVD, as in the current study.…”
Section: Discussionsupporting
confidence: 81%
“…Subsequently, Turcot et al 28 modified an existing 14-item FFQ for use in 137 participants (62% with hyperlipidaemia). They reported adjusted Spearman's correlations for ALA of 0.23 and 0.18 for total n3, with values for EPA and DHA of 0.29 and 0.41 respectively, which were consistent with the range of correlations found by Serra-Majem et al More recently Allaire et al 29 reported higher adjusted Spearman correlations of 0.59, 0.59 and 0.55 for EPA, DHA and LCn3, respectively (P o0.01) using a larger range of questions (136 questions with 40 sub-questions) in a sample of 60 men with prostate cancer. The results from the current study are similar to those of Allaire et al, as would be expected based on the greater number of questions used to identify food intakes related to CVD, as in the current study.…”
Section: Discussionsupporting
confidence: 81%
“…Previous FFQs have mainly focused on fatty fish intake, assumed to reflect marine n-3FA consumption better than total fish intake [23][24][25][26][27][28][29][30][31][32][33][34][35]. We hypothesized that a more meticulous approach using weighted response scales based on EPA and DHA content in fatty and lean fish, other seafoods and marine n-3FA supplements would provide a more precise estimation of marine n-3FA consumption.…”
Section: Discussionmentioning
confidence: 99%
“…This web-FFQ contains standardized photographs of most food items, to help the participant quantify portion sizes, and was developed and validated specifically for Quebec citizens, who constitute the totality of our study population [33]. We also previously validated ability of this web-FFQ to assess ω3 intake specifically in PCa patients [34].…”
Section: Methodsmentioning
confidence: 99%